2015
DOI: 10.1038/modpathol.2014.106
|View full text |Cite
|
Sign up to set email alerts
|

mRNA biomarker detection in liquid-based cytology: a new approach in the prevention of cervical cancer

Abstract: Several high-risk human papillomavirus (HPV)-induced cell biomarkers have been proposed as possible candidates to identify patients harboring high-grade squamous intraepithelial lesions (HSILs) of the uterine cervix. We aimed to determine the feasibility of the detection of the mRNA of six biomarkers in cervical smear specimens obtained by liquid-based cytology and to evaluate whether this approach might be useful in the identification of patients with HSIL. One-hundred and twenty three women referred to colpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 37 publications
1
22
0
Order By: Relevance
“…The largest efficiency gains occur when specificity is low (60%), sensitivity is high (95%), and prevalence is approximately 20%. For example, messenger RNA has a high sensitivity and low specificity for diagnosing early stage cervical cancer (Del Pino et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The largest efficiency gains occur when specificity is low (60%), sensitivity is high (95%), and prevalence is approximately 20%. For example, messenger RNA has a high sensitivity and low specificity for diagnosing early stage cervical cancer (Del Pino et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…For this validation study we considered the following three diagnostic categories as concordant results: (a) negative (control group): normal anal cytology result and negative HPV test; (b) LSIL: anal cytology result of LSIL and biopsy confirming LSIL/AIN1; and (c) HSIL/AIN: anal cytology result of HSIL and biopsy confirming HSIL/AIN2-3 [12,19]. The following were considered as exclusion criteria: (1) previous history or histological diagnosis of anal cancer in the simultaneous biopsy; (2) previous treatment for HSIL/AIN2-3 performed within the previous 3 years; and (3) previous HPV vaccination.…”
Section: Study Design and Case Selectionmentioning
confidence: 99%
“…The detection of host-cell mRNA biomarkers involved in DNA replication and cell cycle progression, such as TOP2A, and other HPV-induced cell molecules involved in cell cycle control, such as MKi67 or p16 (CDKN2A), has proved to be feasible in cervical samples preserved in liquid-based cytology media [12]. Moreover, previous studies have shown that these biomarkers are potentially useful in the detection of intraepithelial lesions of the uterine cervix.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors do cite a potential application involving screening for human papillomavirus (HPV) where Sp is low. However, the study described in del Pino et al () does not use group testing, and we are unaware of any assay that tests for HPV in pools.…”
mentioning
confidence: 99%